Poland : Report on the Observance of Standards and Codes on Accounting and Auditing Update - World Bank Group (World Bank, Vienna, 2015)
Reports on the Observance of Standards and Codes (ROSC) Accounting and Auditing (AA) assess accounting and auditing practices in participating countries. They form part of a joint initiative that is implemented by the World Bank and the International Monetary Fund to review the quality of implementation of twelve internationally recognized core standards (the ROSC Program). These standards and their related codes are relevant to economic stability, and private and financial sector development. The program was developed at the end of the 1990s, in the wake of financial crises that affected many countries in several regions of the world. In the case of the ROSC AA for Poland, the international standards used as benchmarks are (i) relevant portions of European Union legislation (also called the acquis communautaire), (ii) International Financial Reporting Standards (IFRS), (iii) clarified International Standards on Auditing (ISA), (iv) the International Federation of Accounts (IFAC) Code of Ethics, and (v) other international good practice in the field of accounting and auditing regulation. This is the third ROSC AA for Poland. The first two were conducted in 2002 and 2005. This report updates the findings of the 2005 report, and assesses the extent to which prior recommendations have been implemented. Since its inception in the early 2000s, the ROSC AA program has concluded evaluations in more than one hundred countries around the world. ROSC AA reports have been produced for all countries of the Europe and Central Asia region, except the Russian Federation. This ROSC AA serves three main objectives: (i) to support Poland’s development strategy, particularly regarding the enhancement of economic competitiveness, (ii) to assess progress achieved under the Financial Reporting Technical Assistance Program (FRTAP), and (iii) to update the findings of the 2005 ROSC AA. The FRTAP is a Swiss-funded program aimed at strengthening accounting and auditing practices in Poland through the implementation of high quality standards in these areas.